Cinematic darkness: dreaming across film and immersive digital media (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
As with films previously, claims are being made today about the capacity of immersive environments, including virtual reality, to offer viewers or experiencers effective simulations of altered states of consciousness. In this article, we look anew at the enduring question of time-based mechanical (lens based and digital) media’s ability not merely to take us outside of or besides ourselves, but to generate an imaginary realm of their own. Our analysis centres on the use of darkness. Often associated with the passage from one state of consciousness to another, darkness has become a prevalent aesthetic in cinematic immersive media. In some ways, as we will see, the latest technologies of audio-vision appear less apt than conventional cinema to induce us to “cross the bridge” and venture into the land of phantoms. In others, they emerge as privileged entries into the dreamlike worlds of our contemporary, technologized era. In spite of differences in viewing conditions, we find that between the older medium of 2D film and that of cinematic virtual reality, darkness, combined with the illusion of depth and visual replication of motion proves to be a particularly potent harbinger of altered states.
Keywords: Cinema; Darkness; Spectatorship; Dream; Consciousness